The Psychological Impact of Instagrammable Cafe Interiors: The Case of a Santorini-Themed Room - Ramadhina, Rizka Aulia; Sakya, Kharista Astrini (Journal of Architectural Research and Design Studies, 2026)
Contemporary cafe interior design not only serves as an aesthetic element but also plays a significant role in shaping visitors' emotional experiences. This study examines the influence of Instagrammable cafe interior design on visitors' emotional responses from a psychological perspective. The objectives of this study are to analyze the impact of interior design elements on cafe visitors' emotional reactions, examine the concept of Instagrammability as a factor influencing cafe visitors' perceptions and emotions, and identify opportunities for visitors to reorder and revisit the cafe. This study employs a descriptive qualitative approach, utilizing semi-structured interviews and field observations to collect data from two Gen-Z cafe visitors. This study utilizes Don Norman's emotional design theory, which is divided into three levels: visceral, behavioural, and reflective. The results of this study indicate that design elements such as colour, lighting, and spatial concepts are positively correlated with increased positive emotions in visitors. These findings also strengthen the role of interior design as a visual communication medium creating an emotional atmosphere in cafe spaces that supports daily activities, relaxation, and digital activities such as sharing photos on social media. The results of this study can be a reference for interior designers and cafe owners in designing spaces that are not only visually appealing but also consider the psychological aspects of the space's users.